Teoria da complexidade: uma contribuição para o serviço social - Roberto, Ana Carla Junqueira Meirelles (2008)
This thesis is the result of a study about the theory of complexity which has as creator and sistematizator the French sociologist Edgar Morin. The main objective of this study is to research the possibility of a social worker professional intervention, in light of the theory of complexity, and the object of study is to conduct an analysis on the professional practice, from such theoretical and methodological proposal. We, therefore, carried out a survey with social workers attached to the Reference Centre for Social Welfare Vila Industrial, São José dos Campos. The study attempted to identify the most significant components that the subjects in question attach to professional practice, as well as the necessary underlying knowledge for the exercise of professional intervention. A multidimensional methodology of research was employed, attempting to understand the phenomena in its scale with the willingness to experience and interact in the context investigated, observe and be observed, seeking to identify the contents able to clarify the subject under study. Through statements, the study attempted to find the connections and expressions of different ways of thinking about professional practice, linking them to possible contributions which the theory of complexity could bring to Social Service. This is, therefore, a qualitative research which was being built on the way. It could be observed that the daily life of social workers shows the need for a broader theoretical apparatus in order to meet the demands brought by the users; Nowadays, the theory of complexity represents a significant contribution to acknowledge the difficult reality of contemporary subject